2019
DOI: 10.1038/s41467-019-12027-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial co-culture with cell signaling translator and growth controller modules for autonomously regulated culture composition

Abstract: Synthetic biology and metabolic engineering have expanded the possibilities for engineered cell-based systems. The addition of non-native biosynthetic and regulatory components can, however, overburden the reprogrammed cells. In order to avoid metabolic overload, an emerging area of focus is on engineering consortia, wherein cell subpopulations work together to carry out a desired function. This strategy requires regulation of the cell populations. Here, we design a synthetic co-culture controller consisting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 47 publications
(53 reference statements)
1
88
0
1
Order By: Relevance
“…Surprisingly, the role and the consequence of the QS molecules, well described in pure culture, are poorly investigated and understood in bacterial consortia, closer to those found in Nature. Recently one study investigates this question using mathematical model to demonstrate/ propose how QS control the population trajectories in synthetic consortium 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the role and the consequence of the QS molecules, well described in pure culture, are poorly investigated and understood in bacterial consortia, closer to those found in Nature. Recently one study investigates this question using mathematical model to demonstrate/ propose how QS control the population trajectories in synthetic consortium 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of a burdensome heterologous circuit was regulated, switching between "growth mode" and "production mode" in response to population density (Gupta et al, 2017). It has also been demonstrated that control over the growth rates of one strain, through modulating expression of the ptsH sugar transport gene, can be used to control the composition of co-cultures (Stephens et al, 2019). A similar approach was used to distribute a naringenin production pathway between two strains (Dinh et al, 2020).…”
Section: Building Stable Communitiesmentioning
confidence: 99%
“…Centralized treatment plants can then monitor and mediate chemical run-off using networked biological-pods, (“bPods”), equipped with electrochemical sensors, engineered cells, and wireless transmitters ( Stine et al., 2020 ). Similar devices, or in-line microfluidic devices ( Shang et al., 2019 ), could also be used to electronically monitor molecular communication in biomanufacturing with the potential to monitor multiple media components simultaneously, and to direct metabolic use of engineered strains ( Stephens et al., 2019 ; Tsao et al., 2010 ). Each of these systems demonstrates that either in single devices, or networked devices, there are immediate applications for electronically actuated biomolecular communication.…”
Section: Introductionmentioning
confidence: 99%